Structure guided drug design to develop kallikrein 5 inhibitors to treat Netherton syndrome. Issue 12 (15th June 2019) - Walker, Ann L.; Bingham, Ryan P.; Edgar, Emma V.; Ferrie, Alan; Holmes, Duncan S.; Liddle, John; Polyakova, Oxana; Rella, Monika; Smith, Kathrine J.; Thorpe, James H.; Wang, Yichen; White, Gemma V.; et al.
Graphical abstract: Abstract: The connection between Netherton syndrome and overactivation of epidermal/dermal proteases particularly KLK5 has been well established. To treat sufferers of this severe condition we wished to develop a topical KLK5 inhibitor in order to normalise epidermal shedding and reduce the associated inflammation and itching. In this paper we describe structure-based optimisation of a series of brightly coloured weak KLK5 inhibitors into colourless, non-irritant molecules with good KLK5 activity and selectivity over a range of serine proteases.